Impact of The Russian–Ukraine War on Market Values The Food and Beverage Sub-Sector In Indonesia - Ariani Patalle; Mursalam Salim (Faculty of Business and Economics , Universitas Yapis Papua, 2024)
The Russia - Ukraine war that occurred on February 24, 2022 has great influence serious to the global economy in the whole world. The war between the two countries is one of the suspected factors that can influence the value of shares on the capital market. Study this using daily stock price data on food and beverage sub-sector companies in Indonesia, with period observation February 2022. This research uses a purposive sampling technique with the criteria and consideration determined by the researcher so that the samples that fall within these criteria are 38 samples. Collected data using studies documentation with period observation 7 values market company 7 days before And after broke war Russia-Ukrania. Method analysis on research data uses analysis paired sample t-test. Results study find that happened war Russia-Ukrania had no impact on the change mark market company.